A cross-sectional analysis of the short-term outcomes of patients receiving prehospital treatment for symptomatic hypoglycaemia in Cape Town - Booley, Mohammed Ridhaa (Division of Emergency Medicine, 2014)
Includes abstract. Includes bibliographical references.